Carbohydrate Intake, Fiber Intake, and Physical Activity in Relation to Central Obesity in Female Cigarette Factory Workers in Kudus, Central Java - Purbowati, Purbowati; Laili, Irma Wahyu Fikri Miftuchatul; Hidayah, Noor; Istifaizah, Nur (Journal of Applied Food and Nutrition, 2025)
Background: Central obesity in female workers affects helath and work productivity. Abdominal circumference is one of the parameters to determine central obesity. Central obesity is influenced by carbohydrate intake, fiber intake, and physical activity. The study aimed to determine the relationship between carbohydrate intake, fiber intake, and physical activity with abdominal circumference of female workers at the Sukun Cigarette Factory. Research Methods: The design of this study is a correlation description with a cross-sectional approach. The instruments used are semi-quantitative food frequency questionnaire (SQ-FFQ) to measure carbohydrate and fiber intake, global physical activity questionnaire (GPAQ) to measure physical activity, and metline to measure waist circumference. The population is 2562 female workers in the production section. The sample is 346 people (based on the Slovin formula), taken using the cluster sampling technique for each section. Spearman rank data analysis to test the relationship between independent and dependent variables. Research Result: The results showed that 80.9% of subjects had a deficit in carbohydrate intake, 86.4% had a deficit in fiber intake, 45.7% had moderate physical activity, and 67.6% had central obesity. There was no relationship between carbohydrate intake and abdominal circumference, but there was a relationship between fiber intake and physical activity and abdominal circumference. Conclusion: Female workers at the Sukun Cigarette Factory need a balanced nutritious diet and increased physical activity to prevent central obesity.